(untitled) (Research, Society and Development, 2022)
Bariatric surgery is a surgical intervention indicated for severe cases of obesity, a chronic disease triggered by excessive weight gain, which can be associated with other diseases that directly affect human quality of life. In this sense, with a focus on minimizing the risks of weight regain, the present work aims to show the necessary care in post-bariatric surgery, highlighting the main complications that occur after the surgery, which can trigger weight gain again. This is a bibliographic review, with a qualitative approach, carried out in the online databases Biblioteca Virtual em Saúde (BVS BRASIL) and Scientific Electronic Library Online (Scielo), using the keywords: Bariatric surgery; Obesity; Weight reduction; Gastrectomy. In view of the findings, the need for information and awareness of patients regarding food and mental health care was perceived, so that there are no major complications in the post-surgical period and there is a resumption of the patient’s initial condition of obesity.